If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(t + -5) + 8t = 9t + -1 Reorder the terms: -5(-5 + t) + 8t = 9t + -1 (-5 * -5 + t * -5) + 8t = 9t + -1 (25 + -5t) + 8t = 9t + -1 Combine like terms: -5t + 8t = 3t 25 + 3t = 9t + -1 Reorder the terms: 25 + 3t = -1 + 9t Solving 25 + 3t = -1 + 9t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-9t' to each side of the equation. 25 + 3t + -9t = -1 + 9t + -9t Combine like terms: 3t + -9t = -6t 25 + -6t = -1 + 9t + -9t Combine like terms: 9t + -9t = 0 25 + -6t = -1 + 0 25 + -6t = -1 Add '-25' to each side of the equation. 25 + -25 + -6t = -1 + -25 Combine like terms: 25 + -25 = 0 0 + -6t = -1 + -25 -6t = -1 + -25 Combine like terms: -1 + -25 = -26 -6t = -26 Divide each side by '-6'. t = 4.333333333 Simplifying t = 4.333333333
| 312x-143x=428 | | (x-1)(x-5)(x-6)=0 | | 864+.8xy=y | | 5x-8x=-5 | | 27+5=19 | | (2h-6)/6=2/3 | | 0.4b=-2 | | .40x+.20(30)=.20(102) | | 9x-2(x+1)=12 | | 0=(3x-8)*lnx | | n+8=16-4 | | -6(x-7)-7=35 | | 8(2w-6)+7(-y+5)=-8 | | n+5=13-8 | | Log(16)32-log(16)2=x | | 3p^2-5p=4p^2-35p+56 | | 2(x-4)=2x+3x | | 12(s+5)=7.5 | | 20x-2=36x+2 | | n^2+8n-7=0 | | 7w^2+3=-10w | | 36=16x-12x | | 4(2x)=40 | | 3x^2+x-0.5=0 | | 2(3x)=36 | | 10x+6y=16 | | -7x^2-18x+0=0 | | 2z-67=-21 | | 8-(-4)+5=12 | | 7n+3-5n=3n-6 | | V=3.14v^2h | | (25)(7)+x=175 |